T cells reactive with the NC16A domain of BP180 are present in vulval lichen sclerosus and lichen planus. - Baldo, M; Bailey, A; Bhogal, B; Groves, R; Ogg, G; Wojnarowska, F (2010)
BACKGROUND: Lichen sclerosus (LS) is a chronic inflammatory skin condition. The recent demonstration of circulating autoantibodies to extracellular matrix protein 1 and to basement membrane zone (BMZ) components, chiefly BP180, suggests that autoimmunity to these components might contribute to pathogenesis. However, there is no binding of autoantibodies in vivo and as LS is characterized by a lymphocytic infiltrate, it seems likely that LS is mediated, in part, by antigen-specific lymphocytes. Similar mechanisms may apply to vulval lichen planus (LP), an interface dermatitis, with clinical and immunological overlap with LS. OBJECTIVES: This study aims to test the hypothesis that T cells reactive with the NC16A domain of BP180 are present in the peripheral blood of patients with vulval LS and LP. METHODS: Isolated peripheral blood mononuclear cells from 14 patients with vulval LS, 5 with vulval LP and 4 healthy controls were grown in vitro. We examined for immunogenicity of overlapping peptides spanning the NC16A domain of BP180 using interferon-gamma enzyme-linked immunospot assay (ELIspot) on the cultured T-cell lines. BMZ antibodies were assayed, HLA type determined and clinical parameters noted. RESULTS: Significant interferon-gamma production was observed in response to the NC16A peptides in 6 of the 14 vulval LS and 2 of the 5 LP patients, but not in the control subjects. There was an associated autoantibody response to BP180 in 3 LS and 1 LP patient with T-cell responses. These data suggest that in some vulval LS and LP patients, NC16A domain-specific T cells circulate at sufficiently high frequency to be detectable in vitro and show rapid effector function. There was no association with HLA type or clinical parameters. CONCLUSION: We have demonstrated that in > 40% of our vulval LS and LP patients, the NC16A domain of BP180 is a target for circulating T cells, and in vulval LS and LP there are associated autoantibodies to BP180.